Clinicohematological Profile of Patients with Bicytopenia - Murshed, Najib Muaamer Faed; Bhat, Shubha P. (Journal of Health and Allied Sciences NU, 2024)
Background Bicytopenia (BC) is a reduction in counts in any of two cell lineages of blood, which can be a combination of anemia with thrombocytopenia, anemia with leukopenia, or leukopenia with thrombocytopenia. The etiology of BC can be a malignancy, nonmalignant disease, infectious cause, or drug-induced.Aim To assess the clinicohematological profile in patients with BC.Materials and Methods This prospective study was conducted in the hematology laboratory at the Justice K.S. Hegde Charitable Hospital. Patients with BC detected during the analysis of blood for any clinical condition were included in the study. Blood parameters assessed were hemoglobin, red blood cell count, total leukocyte count, and platelet count.Results In this study, 86 patients' samples with BC were collected, out of which 55.8% were male, and 44.2% were female. The most common BC was anemia with thrombocytopenia (69.8%). The most common etiology of BC was found to be nonmalignant (37.2%), followed by malignant (37.2%), infectious (25.6%), and drug-induced (4.7%) cases. Most of the patients with BC presented with fever, pallor, and generalized weakness.Conclusion Anemia with thrombocytopenia emerged as the predominant form of BC in the nonmalignant group, while the malignant etiology group presented with anemia with leukopenia. The infectious etiology group presented with leukopenia with thrombocytopenia. Neonatal sepsis emerged as the most prevalent cause of BC in the age group younger than 10 years, viral fever in the age group of 10 to 39 years, acute lymphoblastic leukemia in the age group of older than 70 years, and chronic liver disease in patients aged between 40 and 69 years.
Keywords: bicytopenia; malignant; nonmalignant; infectious; drug-induced